Reversible Medical Image Watermarking for Tamper Detection and Recovery with Run Length Encoding Compression - Liew, Siau-Chuin; Liew, Siau-Way; Jasni, Mohamad Zain (World Academy of Science, Engineering and Technology, 2010)
Digital watermarking in medical images can ensure the authenticity and integrity of the image. This design paper reviews some existing watermarking schemes and proposes a reversible tamper detection and recovery watermarking scheme. Watermark data from ROI (Region Of Interest) are stored in RONI (Region Of Non Interest). The embedded watermark allows tampering detection and tampered image recovery. The watermark is also reversible and data compression technique was used to allow higher embedding capacity.